Концептосистема сучасного англомовного гастрономічного рекламного естетичного дискурсу - Hafu, Tetiana (Рута, 2021)
The article presents a study that allowed us to construct a cognitive map of modern English gastronomic advertising aesthetic discourse. The main features in the understanding of gastronomic advertising discourse by the representatives of the English-speaking community – gourmet aesthetes are analyzed. The research material for the modern English gastronomic advertising aesthetic discourse was the gastronomic Internet texts of the social network Instagram, which contained a particularly expressive specific aesthetic component. It is established that the mental framework of the cognitive space of a modern English gourmet esthete is formed by 48 significant discourse-creating autochthons-concepts (sensations, emotions, recipe, ingredient, taste and others). The separation of the constants of the concept system of modern English gastronomic advertising aesthetic discourse – generative autochthonous concepts was carried out through the inventory of texts, fixation of objectifiers of concepts and their grouping into semantic areas. To verify the objectivity of the facts, a quantitative method of calculation is used, the criterion χ2.
CONCEPTSYSTEM OF MODERN ENGLISH GASTRONOMY ADVERTISING AESTHETIC DISCOURSE
Keywords: дискурс; рекламний дискурс; гастрономічний дискурс; когнітивне картування